Local Anesthetic Lidocaine and Cancer: Insight Into Tumor Progression and Recurrence - Zhang, Caihui; Xie, Cuiyu; Lu, Yao (Frontiers in Oncology, 2021)
Cancer is a leading contributor to deaths worldwide. Surgery is the primary treatment for resectable cancers. Nonetheless, it also results in inflammatory response, angiogenesis, and stimulated metastasis. Local anesthetic lidocaine can directly and indirectly effect different cancers. The direct mechanisms are inhibiting proliferation and inducing apoptosis via regulating PI3K/AKT/mTOR and caspase-dependent Bax/Bcl2 signaling pathways or repressing cytoskeleton formation. Repression invasion, migration, and angiogenesis through influencing the activation of TNFα-dependent, Src-induced AKT/NO/ICAM and VEGF/PI3K/AKT signaling pathways. Moreover, the indirect influences are immune regulation, anti-inflammation, and postoperative pain relief. This review summarizes the latest evidence that revealed potential clinical benefits of lidocaine in cancer treatment to explore the probable molecular mechanisms and the appropriate dose.